Efektivitas Refreshing Pre dan Post Coference di Ruang Rawat Inap - Sumaryani Ayu Lestari; Muadi Muadi; Dewi Erna Marisa (STIKES Columbia Asia Medan, 2026)
Pre-conference and post-conference are essential components of nursing management functions that play a significant role in enhancing communication, team coordination, continuity of nursing care, and patient safety. However, their implementation in inpatient wards continues to face several challenges, including high nursing workloads, limited time availability, and suboptimal adherence to Standard Operating Procedures (SOPs). This study aimed to analyze the effectiveness of a refresher program on the implementation of pre-conference and post-conference activities in an inpatient ward. A descriptive case study design was employed involving 21 nurses as research participants. Data were collected through direct observation, in-depth interviews, and document review of pre-conference and post-conference practices before and after the intervention. The refresher intervention consisted of SOP education, interactive discussions, and role-play sessions focusing on the proper implementation of pre-conference and post-conference activities. The findings demonstrated a notable improvement in the implementation of both activities following the intervention, as reflected by increased compliance with SOPs, enhanced nurses' understanding of conference procedures, and improved communication and coordination among nursing staff. The Wilcoxon Signed Ranks Test revealed a statistically significant difference between pre- and post-intervention conditions (p < 0.001), indicating that the refresher program was effective in improving the implementation of pre-conference and post-conference activities. These findings suggest that regular refresher programs may serve as a sustainable strategy for improving the quality of nursing services and promoting patient safety in inpatient settings.